Cubicle Refusal in Norwegian Dairy Herds - Myren HJ; Kjæstad HP (Acta Veterinaria Scandinavica, 2001)
In order to survey the behaviour of choosing the alley area instead of a cubicle as a lying place (cubicle refusal), a questionnaire was sent to the 273 dairy farms in Norway known to keep cows in cubicle housing systems. Sixty-six percent of the farmers contacted were included in the study. The median herd size was 18 cows (range 7–118). More than 85% of the herds had sheds providing one or more cubicles per cow. The mean herd occurrence of cubicle refusal was 6%, but showed great variation (range 0–55%). Regression analysis showed a significant association between rearing heifers in slatted floor pens and an increased cubicle refusal occurrence (p = 0.02, R2 = 0.05), while herd size, use of litter, or cubicle-to-animal ratio were not found to be associated with cubicle refusal. The practice of rearing heifers in slatted floor pens accounted for about one half of the observed cubicle refusal (etiologic fraction = 0.51).